Secondary resistance to anti-EGFR therapy by transcriptional reprogramming in patient-derived colorectal cancer models - Vangala, Deepak; Ladigan, Swetlana; Liffers, Sven T.; Noseir, Soha; Maghnouj, Abdelouahid; Götze, Tina-Maria; Verdoodt, Berlinda; Klein-Scory, Susanne; Godfrey, Laura; Zowada, Martina; Huerta, Mario; Edelstein, Daniel L.; et al. (Genome medicine, 2021)
The development of secondary resistance (SR) in metastatic colorectal cancer (mCRC) treated with anti-epidermal growth factor receptor (anti-EGFR) antibodies is not fully understood at the molecular level. Here we tested in vivo selection of anti-EGFR SR tumors in CRC patient-derived xenograft (PDX) models as a strategy for a molecular dissection of SR mechanisms.
Gesehen am 28.10.2021